Dato' Sri Abdul Aziz: Chart our own track to excellence - Mohd R, Jamaludin
“We can chart our own track to excellence,” was the firm stance made by Dato’ Sri Abdul Aziz Abdul Rahman, one of the directors on the board of Universiti Malaysia Pahang (UMP).